PENGEMBANGAN INTERACTIVE DIGITAL BOOK MATAKULIAH KALKULUS PADA MATERI FUNGI EKSPONENSIAL - Andari, Tri (JURNAL LEMMA, 2024)
This research aims to develop and produce a quality Interactive Digital Book in terms of validity, practicality and effectiveness in calculus courses. The research was carried out by the Informatics Engineering study program at PGRI Madiun University. The research steps are guided by the Borg and Gall model. The results of the research are 1) the Interactive Digital Book is declared very valid with an average assessment result by media validators of 85.33%, 2) the Interactive Digital Book is declared very practical as obtained from student response questionnaires with an average value of 80.00%, 3) The Interactive Digital Book was declared effective, with an average score of 92.08, while the percentage of student learning completion results was 92.85%, thus the Interactive Digital Book was said to be effective. So the Interactive Digital Book on exponential functions is suitable for use in calculus courses.